Breast milk and cognitive development—the role of confounders: a systematic review - Walfisch, Asnat (BMJ Publishing Group, 2013)
OBJECTIVES: The association between breastfeeding and child cognitive development is conflicted by studies reporting positive and null effects. This relationship may be confounded by factors associated with breastfeeding, specifically maternal socioeconomic class and IQ. DESIGN: Systematic review of the literature. SETTING AND PARTICIPANTS: Any prospective or retrospective study, in any language, evaluating the association between breastfeeding and cognitive development using a validated method in healthy term infants, children or adults, was included. PRIMARY AND SECONDARY OUTCOME MEASURES: Extracted data included the study design, target population and sample size, breastfeeding exposure, cognitive development assessment tool used and participants’ age, summary of the results prior to, and following, adjustment for confounders, and all confounders adjusted for. Study quality was assessed as well. RESULTS: 84 studies met our inclusion criteria (34 rated as high quality, 26 moderate and 24 low quality). Critical assessment of accepted studies revealed the following associations: 21 null, 28 positive, 18 null after adjusting for confounders and 17 positive—diminished after adjusting for confounders. Directionality of effect did not correlate with study quality; however, studies showing a decreased effect after multivariate analysis were of superior quality compared with other study groupings (14/17 high quality, 82%). Further, studies that showed null or diminished effect after multivariate analysis corrected for significantly more confounders (7.7±3.4) as compared with those that found no change following adjustment (5.6±4.5, p=0.04). The majority of included studies were carried out during childhood (75%) and set in high-income countries (85.5%). CONCLUSIONS: Much of the reported effect of breastfeeding on child neurodevelopment is due to confounding. It is unlikely that additional work will change the current synthesis. Future studies should attempt to rigorously control for all important confounders. Alternatively, study designs using sibling cohorts discordant for breastfeeding may yield more robust conclusions.